(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
This article discusses the problem of wet nurses in Portugal in the eigh- teenth century. In addition to those who were hired by the city to work in charities administrations were many women throughout the eighteenth century played the practice of salaried breastfeeding within urban fam- ilies belonging to the working class. Despite the limited information that exists on this last group of -due to the absence to contractual relations workers, I have tried to provide some notes socio-economic character on them. However, the bulk of the study focuses on drawing the so- cial image of these women constructed from doctors, memorialists and literary discourses (cordel); a nefarious image was projected through different means and instruments of expression (such as work of popular theater or medial treatises). Focus on the speeches about wet nurses is to assume the importance of the process of objectification of their bodies, that is, its conversion into an object of theoretical discussion, instrument or vehicle by which to argue, justify, defend and develop new models in the social body.